A Bridge From the Gut: Azithromycin Links to AMPK/SIRT1 Activation, Rectifies Th17/Treg Balance and Alleviates COPD Associated With Gut Microbiota-TMAO Modulation - Changqing Xu; Guoping Jiang; Guohu Zhang; Jiang Wu; Weiguo Rao; Songtao Jiang; Lanjuan Zhang; Lu Zhang; Yuezhong Shen; Liquan Hong (Discovery Medicine, 2026)
Background: The intestinal microbial ecosystem has emerged as an important contributor to chronic obstructive pulmonary disease (COPD) pathogenesis. Azithromycin (AZI), a commonly used therapeutic agent for COPD, has antibacterial and anti-inflammatory effects. This study aims to explore the mechanism by which AZI regulates the intestinal microbial ecosystem to ameliorate COPD.Methods: A rat COPD model was established by cigarette smoke (CS) exposure. The animals were pretreated with AZI (0.5, 5, 50 mg/kg) with or without the adenosine monophosphate-activated protein kinase (AMPK) inhibitor Compound C. Pulmonary dysfunction and colon injury in COPD rats were evaluated by detecting forced expiratory volume within 0.3 seconds (FEV0.3), forced vital capacity (FVC), as well as hematoxylin and eosin staining. Flow cytometry was used to detect T helper 17 (Th17)/regulatory T (Treg) cell balance in colon tissue. Inflammatory factors and secretory IgA (sIgA) levels were detected using quantitative real-time polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA). Trimethylamine N-oxide (TMAO) content was determined by liquid chromatography with triple-quadrupole mass spectrometry. AMPK/sirtuin 1 (SIRT1) pathway-related proteins were detected using Western blotting.Results: AZI dose-dependently alleviated CS-induced lung dysfunction and colon tissue injury (p < 0.05), reduced the ratio of Th17/Treg, facilitated the expression levels of interleukin (IL)-10 and sIgA, and inhibited the levels of pro-inflammatory factors and TMAO (p < 0.05). In addition, AZI activated the AMPK pathway and upregulated SIRT1 expression in colon tissues (p < 0.05). Critically, the protective effects of AZI were partially reversed by co-treatment with the AMPK inhibitor Compound C (p < 0.05).Conclusion: AZI may regulate the Th17/Treg cell balance in association with TMAO reduction and AMPK/SIRT1 activation, thereby improving intestinal mucosal immunity in COPD rats. These findings highlight the potential of targeting the gut microbiota and mucosal immunity as a therapeutic strategy for COPD management.